Catechin extraction and purification of green tea (Camellia sinensis) and using it in treatment the candida albicans - alasadiy, yassir dakheel (Journal of Kerbala for Agricultural Sciences, 2013)
The extraction and purification Catechin of green tea Camellia sinensis using Separation of retail, as the extraction first with hot water and then hash extracted in two stages first mixed with chloroform and after were obtained at the layer of water, then the second phase mixed with acetate ethyl get disposal from compounds non polar was obtained a brown color dark without viscosity of a substance Catechin has been diagnosed and confirmed using reagents chemicals as well as technical thin layer (TLC) and the amount of Relative movement to the compound (0.76) when using the solution separated acetate ethyl: Benzene (9:11 ) using the technique High Performance Liquid Chromatography(HPLC) have emerged as one package. in the other side applied the catchin as anti mycotic agent, The susceptibility of Candida albicans to catechin were evaluated. The concentrations of catchin causing growth inhibition of tested strains of C. albicans in different zone inhibition .